Migrant mobility and urban transformation: An ethnographic study of transportation infrastructure changes in Makassar - Djufri, Djufri; Arifin, Ansar; Basir, Muhammad (PT Aksara Indo Rajawali, 2025)
The transformation of transportation infrastructure in Makassar—from toll roads and BRT corridors to digital mobility—has significantly altered the city's landscape. However, migrant groups such as online motorcycle taxi drivers, port workers, and street vendors face physical, symbolic, and digital exclusion. This study employs urban ethnography, participatory observation, and route tracing with 32 resource persons. The analysis was carried out through thematic coding, grounded theory, and cross-method triangulation. The results show that top-down built infrastructure often poses mobility barriers, but migrants are not passive: they take alternative routes, build community solidarity, and make tactical use of technology. This practice shapes the infrapolitics of mobility while producing urban space from below. This study enriches the theories of Lefebvre (space production), Urry (the mobility turn), Giddens (structuration), and Gandy (the political ecology of infrastructure), and affirms the importance of the spatial ethnography approach in understanding cities in the global South.